Immunotherapy in elderly head and neck cancer patients: a systematic review and meta-analysis - Salvestrini, Viola; Caini, Saverio; Scricciolo, Melissa; Saerens, Michael; Bollen, Heleen; Bonomo, Pierluigi; Caparrotti, Francesca; Lorini, Luigi; Oliva, Marc; Urbanowicz-Nijaki, Maria; Szturz, Petr (Frontiers in Oncology, 2024)
Introduction: Over the past years, there has been a growing interest in the role of immunotherapy in locally advanced (LA) and recurrent and metastatic head and neck squamous cell carcinoma (R/M HNSCC). High-quality data from prospective trials are lacking for the elderly sub-population. This systematic review and meta-analysis aims to review the efficacy and safety of immunotherapy in older patients. Methods: A systematic literature search was conducted. Randomized clinical trials providing outcome data on a subgroup of elderly (>65y) were available for meta-analysis. Primary outcomes of interest were OS and PFS for efficacy analysis. Results: Seven studies were included in the systematic review, and four in the efficacy analysis. The pooled analysis of OS and PFS showed a consistent benefit (HR 0.78 and 0.91, respectively). Conclusions: immunotherapy may be an effective and well-tolerated treatment option in the elderly population, but more prospective and randomized data are needed.